Upaya Meningkatkan Kemampuan Membuat Kalimat Tanya Melalui Metode Tutor Sebaya di Kelas I Sekolah Dasar Negeri 25 Lubuklinggau - Sumarni Sumarni (Journal of Elementary School (JOES), 2018)
The purpose of this research is to know the application of peer tutor method can improve the ability of second grade students of SD Negeri 25 Lubuklinggau in making a question word. The method used in this research is using the Class Action Research approach (PTK) which is preceded by pratindakan data and twice the implementation of the research cycle. The results of test data on pratindakan of 24 students, students who scored 65 or have completed as many as 14 people or 58.33% of the number of students. While students who scored less than 65 or not completed as many as 10 people or 41.67%, with an average grade of 63.75. In the first cycle there is an increase in value gains. Students who have completed as many as 17 students or 70.83% while unfinished as many as 7 people or 29.17% with an average value of 67.08. This is an increase of 3.33 or 5.23%. Cycle II also increased, from 24 students who have completed as many as 22 students or 91.67% and who have not completed as many as 2 students or 8.33% with an average value of 75.21. If the calculated increase of pratindakan value until cycle II there is an increase of 11.61%. Based on these data the hypothesis that was found in this study proved, that with the application of peer tutor method can improve the ability to make sentences asked students of class I SD Negeri 25 Lubukkinggau. Keywords: Ability, Peer Tutor, Sentence Question